PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.9 SMP NEGERI 20 PEKANBARU - Sandy Novita; Armis '; Syofni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This classroom action research is aimed at improving learning process and improving math learning outcomes by implementing Cooperative Learning Model with Structural Numbered Heads Together (NHT) Approach. The research subjects are 40 heterogenous academic ability level students of the VIII.9 class of State Junior High School 20 Pekanbaru in academic year of 2015/2016. The research consisted of two cycles in which each cycle consisted of four phases, i.e; namely planning, implementing, observing, and reflecting. By the end of a cycle, daily test was held. The data was collected by means of observation and daily test. The action success indicators were if there is learning process improvement and the number of students passing Minimun Completeness Criteria (MCC) indicates the increase after the implementation. The research shows that teachers and students’ activities were conducted well as planned. Most of the students participated actively and responsible in the learning process e.g. discussing, presenting student’s worksheet, responding to classmate’s presentation, and drawing the lesson conclusion. Additionally, the students afforded to answer the written test given by teacher well. Therefore, it can be said that improvement of learning process took place in every meeting. Furthermore, the number of students passing the MCC on base score, first cycle, and second cycle were respectively 40%, 45%, and 67,5%. The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increse. Finally, the research also shows that cooperative learning model with structural Numbered Heads Together (NHT) approach can improve math learning process and learning outcomes of VIII.9 class students at State Junior High School 20 Pekanbaru. Key Words: Math Learning Outcomes, Cooperative Learning Model with Structural Numbered Heads Together (NHT) Approach, Classroom Action Research.